Advanced Characterization of Imiquimod-Induced Psoriasis-Like Mouse Model - Mehwish Jabeen; Anne-Sophie Boisgard; Alix Danoy; Naima El Kholti; Jean-Paul Salvi; Roselyne Boulieu; Bérengère Fromy; Bernard Verrier; Myriam Lamrayah (MDPI AG, 2020)
Many autoimmune disorders such as psoriasis lead to the alteration of skin components which generally manifests as unwanted topical symptoms. One of the most widely approved psoriasis-like animal models is the imiquimod (IMQ)-induced mouse model. This representation mimics various aspects of the complex cutaneous pathology and could be appropriate for testing topical treatment options. We perform a thorough characterization of this model by assessing some parameters that are not fully described in the literature, namely a precise description of skin disruption. It was evaluated by transepidermal water loss measurements and analyses of epidermis swelling as a consequence of keratinocyte hyperproliferation. The extent of neo-angiogenesis and hypervascularity in dermis were highlighted by immunostaining. Moreover, we investigated systemic inflammation through cytokines levels, spleen swelling and germinal centers appearance in draining lymph nodes. The severity of all parameters was correlated to IMQ concentration in skin samples. This study outlines new parameters of interest useful to assess this model. We highlight the skin barrier disruption and report a systemic inflammatory reaction occurring at distance both in spleen and lymph nodes. These newly identified biological endpoints could be exploited to investigate the efficacy of therapeutic candidates for psoriasis and more extensively for several other skin inflammatory diseases.